2020
DOI: 10.1590/0103-8478cr20190806
|View full text |Cite
|
Sign up to set email alerts
|

Altrenogest treatment effects on the reproductive performance of sows during transition to batch farrowing

Abstract: The synthetic progestin altrenogest (ALT) has been widely used in sow farms to concentrate artificial inseminations (AIs) during the transition of weekly productive flow for the batch farrowing system of 14 or 21 days. The objective of the present study was to investigate the effect of the duration of ALT treatment on the reproductive performance of weaned sows during transition to batch farrowing. Retrospective data was evaluated regarding the reproductive performance of primiparous and multiparous sows that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Synchronization-superovulation treatment not only negatively affected pregnancy rates on day 6 of the cycle of sows inseminated during estrus but also decreased the overall pregnancy efficiency, fertilization rate and overall embryo production efficiency by more than 15 percentage points compared to superovulated control sows. Previous studies indicated that a short-term Altrenogest treatment (3-15 days), when administered independently, is effective for grouping the estrus of weaned primiparous and multiparous sows (14,15,40,(51)(52)(53). Moreover, Altrenogest treatment for 14-18 days improved the reproductive performance of gilts by increasing pregnancy and farrowing rates and litter size (35).…”
Section: Discussionmentioning
confidence: 99%
“…Synchronization-superovulation treatment not only negatively affected pregnancy rates on day 6 of the cycle of sows inseminated during estrus but also decreased the overall pregnancy efficiency, fertilization rate and overall embryo production efficiency by more than 15 percentage points compared to superovulated control sows. Previous studies indicated that a short-term Altrenogest treatment (3-15 days), when administered independently, is effective for grouping the estrus of weaned primiparous and multiparous sows (14,15,40,(51)(52)(53). Moreover, Altrenogest treatment for 14-18 days improved the reproductive performance of gilts by increasing pregnancy and farrowing rates and litter size (35).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, using chorionic gonadotropins during lactation may be an alternative to suppress the first post-weaning estrus for a shorter period, allowing the synchronization of the subsequent estrus ( Kirkwood et al, 1999 ; Zemitis et al, 2015 ; Figure 1B ). That would be particularly suitable for herds transitioning from conventional weekly management to batch farrowing ( Corezzolla et al, 2020 ), optimizing labor and facility efficiency.…”
Section: Chorionic Gonadotropinsmentioning
confidence: 99%
“…Nevertheless, such hormones may be administered to lactating sows, which are in lactation-induced anestrous. That would suppress estrus expression after weaning in the treated sows to mitigate the consequences of early weaning or excessive catabolism ( Zemitis et al, 2015 ; Kemp et al, 2018 ) and may also be potentially used to synchronize the postweaning estrus to homogenize the breeding groups, which is necessary in batch farrowing systems ( Zemitis et al, 2015 ; Corezzolla et al, 2020 ). Furthermore, such treatment might allow AI during lactation, contributing to an increase in the number of litters weaned per female per year ( Hausler et al, 1980 ).…”
Section: Introductionmentioning
confidence: 99%